Analyzing the impact of Organizational change in promoting Process Innovation using PLS-SEM -Case study: Algerian Telecom Laghouat - Said Redouane DAHAM; Abdelkader BELLAKHDAR (Journal of Excellence for Economics and Management Research, 2021)
This study aims to show the impact of the organizational change on the process innovation of Algerian Telecom company in Laghouat. We took a sample of 56 individuals who are distributed on different professional categories.  After treating data of a sample of 56 individuals using SmartPLS3, the results show the following: there is a positive impact of the individuals change on the process innovation of the company when the significance level is 5 %. Moreover, there is a positive impact of structure change on the process innovation of the company when the significance level is 5 %. Finally, there is a positive impact of change in technology on the process innovation of the company when the significance level is 5%.